PERANCANGAN INTERIOR YOUTHPRENEUR COWORKING SPACE DI DENPASAR, BALI (Jurnal iSpectrum, 2023)
Youthpreneurs and youth in Denpasar need facilities that can be used to organize or exchange ideas. One of the facilities to carry out these activities is a coworking space. It is hoped that the required coworking space can accommodate work activities in an area and attract the enthusiasm of creative workers to be creative and exchange ideas. With a design approach where data is collected in several ways such as field data studies, typological data, literature data, and literature studies, then proceed to identify where to focus on compiling the data that has been sought. After that, the idea generation process is carried out in the form of centralizing design ideas. After that, the idea generation process is carried out in the form of focusing on design ideas. Then testing is carried out with the aim of providing input. The interior design is a Coworking Space designed with smart – open space so that work activities can be interconnected and accommodated in one place without any meaningful partitions. Not only that, the coworking space is made to have various facilities to attract the enthusiasm of creative workers such as meeting rooms and communal rooms that can be used to exchange ideas for the public interest. Communal space is a space used for conferences and similar activities. While the meeting room can be used for meetings and the like.